2011
DOI: 10.1111/j.1365-2672.2011.05189.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aeromonas caviae polyhydroxyalkanoate synthase gene in Burkholderia sp. USM (JCM15050) enables the biosynthesis of SCL-MCL PHA from palm oil products

Abstract: Aims:  Burkholderia sp. USM (JCM15050) isolated from oil‐polluted wastewater is capable of utilizing palm oil products and glycerol to synthesize poly(3‐hydroxybutyrate) [P(3HB)]. To confer the ability to produce polymer containing 3‐hydroxyhexanoate (3HHx), plasmid (pBBREE32d13) harbouring the polyhydroxyalkanoate (PHA) synthase gene of Aeromonas caviae (phaCAc) was transformed into this strain. Methods and Results:  The resulting transformant incorporated approximately 1 ± 0·3 mol% of 3HHx in the polymer whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…Some exceptions were observed; in literature it was reported that several class I PhaCs may produce scl-mcl-PHA. PhaCAc is considered as one of the most successful enzymes used for scl-mcl-PHA production, while Class IV PHA synthases from Bacillus cereus type (IVc) [Chee et al, 2012;Mezzolla and Poltronieri, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Some exceptions were observed; in literature it was reported that several class I PhaCs may produce scl-mcl-PHA. PhaCAc is considered as one of the most successful enzymes used for scl-mcl-PHA production, while Class IV PHA synthases from Bacillus cereus type (IVc) [Chee et al, 2012;Mezzolla and Poltronieri, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial synthesis of PHB from the C1 resource is a potential way to address the issue (Chee et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…(Chee et al, 2010). Plastic degradation by microbes due to the activity of certain enzymes that cause cleavage of the polymer chains into monomers and oligomers.…”
Section: Introductionmentioning
confidence: 99%